PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWAKELAS VIII SMPN 4 SIJUNJUNG - Amaliah, Jesi Kurnia; K, Delsi; Febriana, Rina (STKIP PGRI Sumbar, 2013)
Â The bagkround in this research is the lower understanding of math concept of student. The goal of this research is to know whether studentâs math concept understanding by appying Guided Note Taking Strategy with Quiz better than the students math concept understanding by applying conventional learning to students VIII (eight) grade junior high school 4 Sijunjung. The research did in August, 28 until September, 13 2013. The kind of this research in experiment research. The population in this research is students VIII grade junior high school 4 Sijunjung. The sample technigue in this research randomized sample technique, as experiment class is VIII.1Â and VIII.2 as control class.Â The instrument in this research is quiz and final test with indicator concept understanding. The test form is used is essay test. The question of final test is eight with reliabilitas 0,91. The students learning result is analyzed by using MINITAB, because p-value < 0,05 then the hypothesis in this research is accepted. It is concluded that the students math concept understanding by applying Guided Note Taking Strategy with Quiz better than the student math concept understanding by applying conventional learningÂ to student VIII grade junior high school 4 Sijunjung.